Social and political struggles in Bolivarian Venezuela - Buzetto, Marcelo (Pontifícia Universidade Católica de São Paulo, 2008)
The political and social struggles in Hugo Chávez’s Venezuela have provoked inumerable polemics on the character of the transformations occuring in that country. We attempt a critical analysis of the Venezuelan situation, taking into consideration, principally, the position of the social and political forces that defend the deepening of the so-called “Bolivarian Revolution”.